Long-term cost effectiveness of ticagrelor in patients with acute coronary syndromes in Thailand - Sukit Yamwong; Unchalee Permsuwan; Sirana Tinmanee (Health Economics Review, 2014)
Objectives: To evaluate the long-term cost-effectiveness of ticagrelor and ASA versus generic and branded clopidogrel and ASA in patients with ACS based on a Thai cost database. Methods: A one-year decision tree and a long-term Markov model were constructed to estimate lifetime costs and quality-adjusted life years (QALYs). For the first year, data from PLATO (NCT00391872) were used to estimate the rate of cardiovascular events, resource use, and QALYs. For year 2 onwards, clinical effectiveness was estimated conditional on individual health states that occurred during the first year. Results: In the base-case analysis, the incremental cost-effectiveness ratio (ICER) with ticagrelor was 292,504 (9,476) and 60,055 (1,946) THB()/QALY compared with generic and branded clopidogrel, respectively. The probability of ticagrelor being cost-effective was above 99% at a threshold of 160,000 THB/QALY compared with branded clopidogrel. Conclusions: This health economic analysis provides cost effectiveness data for ticagrelor compared with both generic and branded clopidogrel in Thailand. Based on this analysis, it appears that ticagrelor is an economically valuable treatment for ACS compared with branded clopidogrel within the Thai context.
Keywords: 330; Cost-effectiveness; Ticagrelor; Acute coronary syndrome; Clopidogrel